ANALISIS EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA INDUSTRI KECIL DAN MENENGAH FURNITUR DI KOTA PEKANBARU - Raihan Hanafi; Harlen '; Azwar Harahap (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aim to know the level of the efficiency of use of production factors at both of group industry. As a result of that, it will be know what production factor that needs for increasing or the reducing of input in order to reach the efficiency.The population of this research is the small and medium furniture industries in Pekanbaru City which the amount of sample in 52 industry unit. The dependent variable that used is financial capital, labour and material, meanwhile the dependent variable is production value. Method of the collecting data is do by questionare. Analysis methid that used in the research is production function of Cobb-Douglas with Frontiers Stochastic Applications and Return to Scale.The result of the furniture from wood show that the technical efficiency is about 0,5008. The allocative efficiency is 1,2742. And the Economic efficiency is 0,638. While for return to scale about 1,0783. It means the furniture from wood is in the increasing return to scale.For the furniture from metal, the level of technical efficiency is about 0,7519, the allocative efficiency is 1,7234, and the economic efficiency is 1,2931. While the return to scale value is about 0,6939. It means furniture from metal is in decreasing return to scale.By the level of technical efficiency that approaching 1(one). It can concluded that furniture from metal industries is more efficient in the using of its factor production than the metal furniture.Keywords : Efficiency, Productions, Cobb-Douglas, and Frontier Stochastic